Zoonyms in Russian and Armenian Compliments - Arshakyan, Mariam (Bulletin of Yerevan University H: Russian Philology, 2026)
The article examines the specific functioning of the lexical-semantic group "zoonyms" in the structure of compliments in Russian and Armenian. It identifies both universal features determined by common human perception and specific national-cultural traits. Special attention is paid to the connotative meanings of words and their morphemic structure, in particular, the role of suffixes in forming additional semantic nuances. The relevance of this study stems from the need for an in-depth study of the mechanisms of metaphorization of natural objects as tools for expressing positive evaluations in different linguistic cultures. The study aims to distinguish between universal and nationally specific cognitive structures that allow the properties of living nature to be projected onto the human personality. A special place is given to the analysis of fauna as axiological reference points defining ideas about beauty, strength, and character traits. The study draws on data from phraseological dictionaries and national corpora. Using comparative, typological and semantic analysis, the author describes the key associative field of "animal world" in compliments. The analysis shows that zoonyms are used more frequently in complimentary expressions by speakers of Russian culture than by speakers of Armenian culture. In Russian, most zoonyms in complimentary expressions are used in diminutive forms. The intensive use of diminutive suffixes leads to a variety of forms for the same zoonym. Meanwhile, in Armenian compliments, possessive forms of zoonyms predominate.